Thymic cyst: Is attenuation artifactually increased on contrast-enhanced CT? - Wang, Chao; Mao, Jin; Yang, Siyu; Xie, Huanhuan; Wang, Shan; Hu, Ling (Frontiers in Oncology, 2022)
Background: Thymic cysts are often misinterpreted as thymomas or lymph nodes, then leading to unnecessary thymectomy. The purpose of this study was to investigate how the adjacent large vessels artifactually affected attenuation values of thymic cysts on contrast–enhanced CT (CE-CT). Methods: In this retrospective study, a total of 84 patients were included with pathological diagnosis of thymic cysts and preoperative CE-CT. Quantitative measurements of the size, CT attenuation of thymic cysts and CT attenuation of adjacent large vessels were performed on preoperative CE-CT. According to the absolute change in attenuation of the cysts between contrast-enhanced and nonenhanced CT, the patients were classified into the groups of artifactual hyper-density, unchanged density, and artifactual hypo-density. CT characteristics were compared between the three groups. Furthermore, multivariable logistic regression analysis was performed to determine the independent factors for artifactual hyper-density. Results: The group of artifactual hyper-density had smaller short diameter of the cysts, higher postcontrast attenuation values and lower nonenhanced attenuation values of the adjacent large vessel. Furthermore, the multivariable logistic analysis showed that artifactual hyper-density of thymic cysts was negatively associated with nonenhanced attenuation of adjacent large vessel, and positively associated with postcontrast attenuation of adjacent large vessel and postcontrast attenuation of cysts. Conclusions: Most cases with >20 HU nonenhanced CT attenuation in surgically resected cases. Artifactual hyper-density─pseudo-enhancement phenomenon of thymic cysts was more apparent in higher increasing attenuation of adjacent large vessels on CE-CT. A well understanding of this phenomenon can help reduce preoperative misdiagnosis and unnecessary thymectomy.